GEOVISUALISASI DATA PERUBAHAN GARIS PANTAI DI KOTA PADANG TAHUN 2000-2020 DENGAN MEMANFAATKAN APLIKASI CARTO BERBASIS WEBGIS - KHAIRUL ZIKRI; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This research aims to (1) to find out the changes in the extent of abrasion and accretion and the length of the coastline in the padang city in 2000-2020 (2) Know how to use Carto to visualize changes in coastline in Padang City (3) Know how to combine data visualization of coastal changes into a WebGIS. The research method used is quantitative descriptive research. The technique of data collection in this study is by means of observation and study of literature. Data analysis techniques are overlay analysis, proximity and geovisuization, the results of this study are (1) The difference in accretion area with abrasion of 180738.37 M compared to 189545.18 M with a change in coastline per year of 51.67 meters. (2) Can be implemented geovisualisai using carto application (3) Use of Codeigniter as a framework and Binarry admin as user interface in the process of integration data visualization of shoreline changes work well and can be connected in webGIS system,